DETERMINING TENDENCIES IN THE COMPETITIVENESS OF RAIL TRANSPORT - Aksenov, I. M. (Science and Transport Progress, 2007)
The classification chart of competitiveness of transporting products is offered on elements. Directions of increase of competitiveness of transporting services and function of marketing-logistic focis of management by transportations are considered.